A randomised controlled trial of supplemental oxygen versus medical air during exercise training in people with chronic obstructive pulmonary disease: supplemental oxygen in pulmonary rehabilitation trial (SuppORT) (Protocol). Issue 1 (December 2016) - Alison, Jennifer; McKeough, Zoe; Jenkins, Sue C; Holland, Anne; Hill, Kylie; Morris, Norman; Leung, Regina; Williamson, Kathleen; Spencer, Lissa M; Hill, Catherine J; Lee, Annemarie L; Seale, Helen; et al.
Abstract Background Oxygen desaturation during exercise is common in people with chronic obstructive pulmonary disease (COPD). The aim of the study is to determine, in people with COPD who desaturate during exercise, whether supplemental oxygen during an eight-week exercise training program is more effective than medical air (sham intervention) in improving exercise capacity and health-related quality of life both at the completion of training and at six-month follow up. Methods/Design This is a multi-centre randomised controlled trial with concealed allocation, blinding of participants, exercise trainers and assessors, and intention-to-treat analysis. 110 people with chronic obstructive pulmonary disease who demonstrate oxygen desaturation lower than 90 % during the six-minute walk test will be recruited from pulmonary rehabilitation programs in seven teaching hospitals in Australia. People with chronic obstructive pulmonary disease on long term oxygen therapy will be excluded. After confirmation of eligibility and baseline assessment, participants will be randomised to receive either supplemental oxygen or medical air during an eight-week supervised treadmill and cycle exercise training program, three times per week for eight weeks, in hospital outpatient settings. Primary outcome measures will be endurance walking capacity assessed by the endurance shuttle walk test and health-related quality of life assessed by the Chronic Respiratory Disease Questionnaire. Secondary outcomes will include peak walking capacity measured by the incremental shuttle walk test, dyspnoea via the Dyspnoea-12 questionnaire and physical activity levels measured over seven days using an activity monitor. All outcomes will be measured at baseline, completion of training and at six-month follow up. Discussion Exercise training is an essential component of pulmonary rehabilitation for people with COPD. This study will determine whether supplemental oxygen during exercise training is more effective than medical air in improving exercise capacity and health-related quality of life in people with COPD who desaturate during exercise. Trial registration Australian New Zealand Clinical Trials RegistryACTRN12612000395831, 5th Jan, 2012